Perovskite fluorescent composite material with shape memory performance and preparation method and application thereof
By combining perovskite quantum dots (PQD) with PLA/PCL shape memory polymer material, a perovskite fluorescent composite material with shape memory properties is formed, which solves the problems of PQD instability and easy leakage of lead elements, and achieves the effect of high fluorescence yield and long service life.
Patent Information
- Application Number
- CN202411623483.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
AI Technical Summary
Perovskite quantum dots (PQDs) have problems with instability and easy leakage of lead elements during the synthesis process, making it difficult to commercialize.
By combining PQD with PLA/PCL shape memory polymer material, a perovskite fluorescent composite material with shape memory properties is formed. The material can return to its initial state under external environmental stimulation, improving the stability of PQD.
It achieves high fluorescence yield and long service life of perovskite materials, and has good shape memory performance, which is suitable for a variety of application fields.
Smart Images

Figure CN119685003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite luminescent composite materials, and in particular to a perovskite fluorescent composite material with shape memory performance, and a preparation method and application thereof. Background Art
[0002] Due to its unique structure and quantum confinement effect, PQD has a series of characteristics such as high fluorescence yield, directly adjustable band gap, short radiation lifetime, etc., making it a strong competitor to replace traditional fluorescent materials and a hot topic in recent research. PQD has been widely used in optics and photonics due to its excellent optoelectronic properties, including perovskite solar cells, Mrico-LEDs, displays, photodetectors, etc. However, due to the instability caused by the dynamic binding of organic long-chain ligands during the synthesis process, and the easy decomposition of its own structure, which leads to the easy leakage of lead elements and causes environmental pollution, PQD is difficult to commercialize. In response to this problem, in recent years, methods such as ion doping, surface modification, and the introduction of other inert materials and PQDs to construct composite materials have been proposed. Among them, constructing composite materials is an effective means to improve the stability of PQDs and reduce lead leakage. According to the unique properties of the selected inert materials, after organically combining with PQDs, more flexible and widely used optoelectronic materials can be developed.
[0003] Among polymer materials, shape memory polymer (SMP) is a new type of smart material. It has the characteristics of both rubber and plastic because of its two-phase structure, namely, a fixed phase that remembers the initial state and a reversible phase that solidifies and softens reversibly with external stimuli. When sensing changes in the external environment, it completes the cycle of "memorizing the initial state-fixing the deformed state-restoring the initial state". According to the different types of changes in the external environment, shape memory polymers can be divided into thermal SMP, electro-induced SMP, photo-induced SMP, chemical sensing SMP, etc. SMP is widely used in the textile industry, medicine, aerospace and other fields due to its low cost, easy processing, good mechanical properties, and corrosion resistance. The organic combination of the two can solve the easy decomposition characteristics of PQD due to its own structure, increase its stability under water, oxygen and light stimulation, and at the same time have the good shape memory properties of SMP.
[0004] However, the full potential of fluorescent materials with shape memory properties in industrial and daily applications has not yet been fully developed. There is an urgent need to develop fluorescent materials with low cost, good shape memory properties and high fluorescence yield to meet market demand. Summary of the invention
[0005] The purpose of the present invention is to provide a perovskite fluorescent composite material with shape memory properties and its preparation method and application, to improve the fluorescence stability of the perovskite material, solve the problem of easy decomposition, and at the same time the composite material has a shape memory function.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] On the one hand, the present invention provides a perovskite fluorescent composite material with shape memory properties, wherein the composite material is obtained by encapsulating PQD with PLA / PCL shape memory polymer.
[0008] Preferably, the PQDs include inorganic perovskite quantum dots and organic-inorganic hybrid perovskite quantum dots, and more preferably inorganic perovskite quantum dots.
[0009] Further preferably, the perovskite structure is a structure having a general chemical formula ABX3, wherein A and B are two different cations and X is an anion.
[0010] Further preferably, the A comprises cesium ions (Cs + ), formamidinium ion (FA + ), methylamine ion (MA + ), wherein B includes Pb 2+ , Cu 2+ Sn 2+ , the X includes I - Br - , Cl - .
[0011] Further preferably, the inorganic perovskite quantum dots include CsPbX3, CsPbCl x Br 3-x , CsPbBr x I 3-x (0≤x≤3).
[0012] Further preferably, the organic-inorganic hybrid perovskite quantum dots include FAPbX3, MAPbX3, FA x Cs 1- x PbX3、MA x Cs 1-x PbX3(0 <x<1)。
[0013] Preferably, the PLA / PCL shape memory polymer is prepared by blending PLA and PCL, and the PLA / PCL shape memory polymer contains C=O for passivating defects in the PQD.
[0014] In a second aspect, the present invention further provides a method for preparing the above-mentioned perovskite fluorescent composite material with shape memory properties, comprising the following steps:
[0015] S1, PLA and PCL are mixed in an organic solvent and a gel solution is obtained after ultrasonication;
[0016] S2, adding the PQD solution dropwise to the gel solution obtained in step S1, firstly magnetically stirring to uniformly mix the two, and then removing bubbles by ultrasound to obtain a mixed solution;
[0017] S3, volatilizing the mixed solution in step S2 in air at room temperature to obtain the perovskite fluorescent composite material.
[0018] Preferably, in step S1, the mass ratio of PLA to PCL is (9-1):1, more preferably (9-4):1.
[0019] Preferably, in step S1, the mass ratio of the total mass of PLA and PCL to the organic solvent is 1:(4-8), more preferably 1:(5-6).
[0020] Preferably, in step S1, the weight average molecular weight of the PLA is 50,000-60,000.
[0021] Preferably, in step S1, the weight average molecular weight of the PCL is ˜80,000.
[0022] Preferably, in step S1, the organic solvent includes chloroform and dichloromethane, and more preferably dichloromethane.
[0023] Preferably, in step S1, the ultrasonication time is 3-8 hours, more preferably 3-5 hours.
[0024] Preferably, in step S2, the concentration of the PQD solution is 0.002-0.188 mol / ml.
[0025] Further preferably, in step S2, the concentration of the PQD solution is 0.002-0.047 mmol / ml.
[0026] Preferably, in step S2, the volume ratio of the PQD solution to the gel solution is (0.05-0.1):1.
[0027] Preferably, in step S2, the magnetic stirring time is 1-3 hours, and the rotation speed is 300-1000 r / min.
[0028] Further preferably, in step S2, the magnetic stirring time is 1-2 hours, and the rotation speed is 300-500 r / min, so that the solution is evenly mixed.
[0029] Preferably, in step S2, the ultrasonic time is 0.5-3h, and the ultrasonic power is 35kHZ-50kHZ.
[0030] Further preferably, in step S2, the ultrasonic time is 0.5 to 1 h, and the ultrasonic power is 35 kHz to 40 kHz to remove bubbles in the solution.
[0031] Preferably, in step S2, the preparation method of the PQD includes a hot injection method and a room temperature method, and the hot injection method is more preferably used.
[0032] Preferably, in step S2, the PQD is added dropwise to the gel solution obtained in step S1 at a speed of 1 to 2 drops per second.
[0033] Preferably, in step S3, the volatilization molding method includes scraping, dripping or spin coating, and scraping is more preferably used.
[0034] In a third aspect, the present invention also provides an application of the above-mentioned perovskite fluorescent composite material with shape memory properties, including application in 3D printing materials, anti-counterfeiting technology materials, and flexible materials.
[0035] Preferably, the perovskite fluorescent composite material uses screen printing technology to print out two-dimensional codes, fingerprints, Morse codes, etc. for application in the field of anti-counterfeiting. The two-dimensional code and fingerprint patterns are printed on a customized template using screen printing technology, and the patterns are clear and stable in the air.
[0036] Preferably, the perovskite fluorescent composite material can be used as ink for 3D printing to print out models with shape memory properties that can change according to external environmental stimuli.
[0037] Preferably, the perovskite fluorescent composite material can be used as a flexible material and applied to diving suits, flexible robots, and flexible sensors.
[0038] The present invention proposes a perovskite fluorescent composite material with shape memory properties. PQD and PLA / PCL shape memory polymer are uniformly mixed, and the solvent is volatilized to prepare a perovskite fluorescent composite material with high fluorescence yield and high shape memory properties. Among them, the shape memory property comes from the PLA / PCL shape memory polymer material. When the external temperature reaches the glass transition temperature of the material, the material can be restored to the initial state. After PQD absorbs ultraviolet light energy, the electrons transition to the excited state, and fluorescence occurs in the process of returning to the ground state in the form of light radiation. And C=O in the shape memory polymer can passivate PQD defects, thereby improving the fluorescence stability of PQD.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention prepares a perovskite fluorescent composite material with shape memory properties, using perovskite nanocrystals - PQD as a luminescent material, which has a high fluorescence quantum yield. At the same time, the C=O of the shape memory material passivates the defects of PQD, and its dense network gives PQD good stability, so that the composite material has a long service life and high shape memory properties.
[0041] (2) The present invention has good luminescence performance, achieves high fluorescence yield, high fluorescence efficiency, the material luminescence is adjustable from blue to red, and has excellent light, water and thermal stability.
[0042] (3) The present invention has sensitive shape memory recovery capability, a recovery time of 1-5s, and strong tensile resistance.
[0043] (4) The present invention is simple to operate, has a short preparation cycle, can realize large-area preparation, and can be prepared into different forms according to actual applications during the preparation process, and has strong processability and practicality.
[0044] (5) The perovskite fluorescent composite material prepared by the present invention can be applied to 3D, 4D printing, anti-counterfeiting and information encryption, flexible robots, flexible sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is the fluorescence spectrum and absorption spectrum of the perovskite fluorescent composite film CsPbBr3Film with shape memory performance in Example 1;
[0046] Figure 2 is the XRD pattern of the perovskite fluorescent composite film CsPbBr3Film with shape memory properties in Example 1;
[0047] Figure 3 is an infrared spectrum of the shape memory polymer material and the PQD before and after mixing in Example 1;
[0048] Figure 4 is a stability diagram of the perovskite fluorescent composite film CsPbBr3Film with shape memory performance in Example 1 under ultraviolet light and in alcohol;
[0049] Figure 5 is a water stability diagram of the perovskite fluorescent composite film CsPbBr3Film with shape memory properties in Example 1;
[0050] Figure 6 is a thermal stability diagram of the perovskite fluorescent composite film CsPbBr3Film with shape memory properties in Example 1;
[0051] Figure 7The shape memory performance of the perovskite fluorescent composite film CsPbBr3Film with shape memory performance in Example 1;
[0052] Figure 8 , Fig. 9 , Fig.10 They are respectively physical recording diagrams of 100 temperature responses of the perovskite fluorescent composite film CsPbBr3Film with shape memory performance in Example 1 at 70°C, 90°C and 100°C;
[0053] Fig.11 This is a real picture of the application of the perovskite fluorescent composite film CsPbBr3Film with shape memory performance in the field of anti-counterfeiting;
[0054] Fig.12 Fluorescence spectrum and absorption spectrum of the perovskite fluorescent composite film CsPbI3Film with shape memory properties in Example 4;
[0055] Fig.13 This is a stability diagram of the perovskite fluorescent composite film CsPbI3Film with shape memory properties in Example 4 under different environments (ultraviolet light, water, alcohol);
[0056] Fig.14 is a thermal stability diagram of the perovskite fluorescent composite film CsPbI3Film with shape memory properties in Example 4;
[0057] Fig.15 The shape memory performance of the perovskite fluorescent composite film CsPbI3Film with shape memory performance in Example 4;
[0058] Fig.16 , Fig.17 They are respectively physical recording diagrams of 100 times of temperature response of the perovskite fluorescent composite film CsPbI3Film with shape memory performance in Example 4 at 90°C and 100°C;
[0059] Fig.18 The perovskite fluorescent composite film CsPbBr with shape memory performance in Example 5 1.5 I 1.5 Fluorescence spectrum and absorption spectrum of Film;
[0060] Fig.19 The perovskite fluorescent composite film CsPbCl with shape memory performance in Example 6 1.5 Br 1.5 Fluorescence spectrum and absorption spectrum of Film;
[0061] Fig. 20The perovskite fluorescent composite films CsPbI3Film, CsPbBr with shape memory properties in Examples 4, 5, and 6 1.5 I 1.5 Film, CsPbCl 1.5 Br 1.5 XRD pattern of Film. DETAILED DESCRIPTION
[0062] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0063] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0064] The weight average molecular weight of PLA used in the following examples is (50,000-60,000), and the weight average molecular weight of PCL is (-80,000).
[0065] Embodiment 1:
[0066] 1. Preparation of PQD (hot injection method), the steps are as follows:
[0067] (1) Preparation of cesium source: Add 0.2 g CsCO3, 5 ml octadecene, and 1.2 ml oleic acid (OA) into a three-necked flask and heat to 110°C under nitrogen.
[0068] (2) Preparation of lead source: 0.188 mmol PbBr2 and 10 ml octadecene were added to a three-necked flask, and vacuum degassed at 120°C for 1 h, followed by addition of 0.5 ml OA and 0.5 ml OAm, and heated to 165°C under nitrogen atmosphere;
[0069] (3) Synthesis of quantum dots: 0.4 ml of cesium source was extracted and injected into a three-necked flask containing a lead source, and the temperature was rapidly cooled in an ice water bath;
[0070] (4) Centrifugation: Divide the solution in the three-necked flask into two parts and place them in centrifuge tubes. After centrifugation, pour out the supernatant, add 2 ml of n-hexane and 6 ml of ethyl acetate to each tube, and centrifuge at 10,000 r for 5 min. Finally, add 2 ml of n-hexane to each tube to dissolve, and a PQD solution can be obtained. The PQD is CsPbBr3 PQDs.
[0071] 2. Preparation of perovskite fluorescent composite material with shape memory properties, the steps are as follows:
[0072] (1) PLA and PCL with a mass ratio of 9:1 were measured, with a total mass of 5 g. The mass ratio of the total mass of PLA and PCL to dichloromethane was 1:5. The three were mixed and placed in an ultrasonicator for 5 h to obtain a gel solution;
[0073] (2) Take 200ul of the PQD solution prepared by the hot injection method above, add it dropwise into 2ml of the gel solution, stir it magnetically for 1h, and then put it into an ultrasonic instrument for 0.5h;
[0074] (3) The solution in step (2) is coated into a thin film by a doctor blade method, and the solvent is evaporated in the air at room temperature to obtain a perovskite fluorescent composite film CsPbBr3Film.
[0075] 3. Characterization of the fluorescent composite film prepared above
[0076] (1) Structural characterization
[0077] Figure 1 The fluorescence spectrum and absorption spectrum of the fluorescent composite film prepared in Example 1. It can be seen from the figure that the exciton absorption peak and maximum fluorescence emission peak of the film are located at 509nm and 520nm respectively, and it emits bright green light under ultraviolet light; the half-peak width of the maximum fluorescence emission peak is 20.49nm.
[0078] Figure 2 This is the XRD spectrum of the fluorescent composite film prepared in Example 1. It can be seen from the figure that the emission peak matches the PDF, proving that the PQD in the film is still an octahedral structure.
[0079] (2) Characterization of passivation mechanism
[0080] Figure 3 This is the Fourier infrared spectrum of the shape memory polymer material before and after mixing with PQD. From the spectrum, we can see that the stretching vibration peak of C=O increases from 1757.72cm -1 Move to 1755.33cm -1 , and the peak intensity weakened, proving that the C=O content in the film decreased and participated in the passivation reaction.
[0081] (3) Stability characterization
[0082] The fluorescent composite film was placed in different environments, namely, under ultraviolet light, in alcohol, in water, and under heating, and the change of PL intensity over time was observed. Figure 4 The PL intensity change of the fluorescent composite film under ultraviolet light and in alcohol for 72 hours is shown, and the PL intensity is maintained at 62.6% and 53.4% of the original value respectively. Figure 5 The water stability of the fluorescent composite film is demonstrated. After being immersed in water for 30 days, the PL intensity is maintained at 85.6% of the original value. Figure 6 The thermal stability of the fluorescent composite film is shown. The PL intensity changes at different temperatures are detected. When the temperature reaches 100°C, the PL intensity is 60.3% of the original. This shows that the fluorescent composite film has enhanced various stabilities under the passivation of the shape memory material.
[0083] (4) Shape memory performance
[0084] The shape memory property of SMP is mainly reflected in that when the temperature reaches the glass transition temperature (Tg), the material can return to its initial state. In the present invention, the external temperature is fixed, the perovskite fluorescent composite film with shape memory properties is heated to a molten state, an external force is applied to change the orientation of the molecular chains in the material to obtain a temporary shape, and then heated to return to the initial state. The "initial shape-temporary shape-restore initial shape" is a temperature response cycle, and the cycle is repeated 100 times in sequence, the change in fluorescence intensity is recorded, and the state and brightness of the fluorescent composite film are recorded by taking pictures. The bent state in the figure is a temporary shape, and the straightened state is restored to the initial shape. The relationship between fluorescence intensity and the number of cycles is shown in the figure. Figure 7 As shown in Figure 2, when the external temperature is 70°C, the PL intensity finally maintains to 61.1% of the original value, and the photo is recorded as follows: Figure 8 As shown in Figure 2, there is no obvious change in the brightness between the initial state and after 100 cycles; when the external temperature is 90°C, the PL intensity finally maintains to 58.2% of the original value, as shown in Figure 2. Fig. 9 As shown; when the external temperature is 100℃, the PL intensity finally maintains to 38.2% of the original value, as shown Fig.10 As shown, after 100 cycles, the fluorescence brightness decreased significantly.
[0085] 4. Application of perovskite fluorescent composite materials with shape memory properties
[0086] The perovskite fluorescent composite material with shape memory properties prepared in Example 1 was used as ink, and a two-dimensional code pattern was printed on dust-free paper used in the laboratory using screen printing technology, as shown in FIG. Fig.11 As shown, anti-counterfeiting is achieved.
[0087] Example 2
[0088] Different from Example 1, the mass ratio of PLA to PCL is 8:2, the total mass is still 5 g, and the remaining steps are the same as Example 1.
[0089] Example 3
[0090] 1. PQD preparation method (room temperature method), the steps are as follows:
[0091] (1) Mix 0.2 mmol of PbBr2 and CsBr, and then add 5 ml of DMF to dissolve;
[0092] (2) Take 1 ml of the solution in step (1) and add 50 ul of OAm and 75 ul of OA;
[0093] (3) Take 100ul of the mixed liquid in step (2), add it dropwise into 5mL of toluene, and stir it magnetically for 5min to obtain a uniformly dispersed PQD solution, wherein the PQD is CsPbBr3 QDs.
[0094] 2. This example adopts a room temperature method to prepare PQDs, thereby preparing a perovskite fluorescent composite material with shape memory properties. The remaining preparation steps are the same as those in Example 1.
[0095] Example 4
[0096] 1. In this Example 4, CsPbI3 QDs were prepared by hot injection method, that is, 0.188 mmol PbI2 was added when preparing the lead source, and the remaining steps were the same as those in Example 1.
[0097] 2. Make a simple characterization of the fluorescent composite film CsPbI3Film prepared in this example. Fig.12 Shown are the fluorescence spectrum, absorption spectrum and physical picture of the composite film. Fig.13 , 14 A graph showing the stability of the film under different environments (UV light, water, alcohol, heat) is shown. Fig.15 This is a graph showing the fluorescence intensity change of the film after 100 cycles of temperature response at 90°C and 100°C. Fig.16 , 17 The state and brightness of the film in response to different temperatures were recorded. Fig. 20 The XRD pattern of the perovskite film CsPbI3Film is shown.
[0098] Example 5
[0099] In this embodiment 5, CsPbBr was prepared by hot injection method. 1.5 I 1.5 QDs, that is, when preparing the lead source, 0.094mmolPbBr2 and 0.094mmolPbI2 were added, and the remaining steps were the same as in Example 1. The physical picture, PL spectrum, and absorption spectrum of the film are shown in Fig.18 , XRD spectrum see Fig. 20 .
[0100] Example 6
[0101] In this embodiment 6, PQDCsPbCl was prepared by hot injection method 1.5 Br 1.5QDs, that is, when preparing the lead source, 0.094mmol PbBr2 and 0.094mmol PbCl2 were added, and the remaining steps were the same as in Example 1. The physical picture, PL spectrum, and absorption spectrum of the film are shown in Fig.19 , XRD spectrum see Fig. 20 .
[0102] In summary, the present invention provides a perovskite fluorescent composite material with shape memory properties, which has strong plasticity, good stability, is not easy to decompose, has excellent shape memory properties, and has good luminescence properties, and can be widely used in anti-counterfeiting, 3D printing, flexible materials and other fields.
[0103] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A perovskite fluorescent composite material with shape memory properties, characterized in that: The composite material is obtained by encapsulating PQD with PLA / PCL shape memory polymer.
2. The perovskite fluorescent composite material with shape memory properties according to claim 1, characterized in that: The PQDs include inorganic perovskite quantum dots and organic-inorganic hybrid perovskite quantum dots.
3. The perovskite fluorescent composite material with shape memory properties according to claim 2, characterized in that: The inorganic perovskite quantum dots include CsPbX3, CsPbCl x Br 3-x 、CsPbBr x I 3-x , wherein X includes I, Br, Cl; the organic-inorganic hybrid perovskite quantum dots include FAPbX3, MAPbX3, FA x Cs 1-x PbX3、MA x Cs 1-x PbX3, wherein X includes I, Br, and Cl.
4. The perovskite fluorescent composite material with shape memory properties according to claim 1, characterized in that: The PLA / PCL shape memory polymer is prepared by blending PLA and PCL. The PLA / PCL shape memory polymer contains C=O, which is used to passivate defects in the PQD.
5. A method for preparing a perovskite fluorescent composite material with shape memory properties as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1, PLA and PCL are mixed in an organic solvent and a gel solution is obtained after ultrasonication; S2, adding the PQD solution dropwise to the gel solution obtained in step S1, firstly magnetically stirring to uniformly mix the two, and then removing bubbles by ultrasound to obtain a mixed solution; S3, volatilizing the mixed solution in step S2 in air at room temperature to obtain the perovskite fluorescent composite material.
6. The method for preparing a perovskite fluorescent composite material with shape memory properties according to claim 5, characterized in that: In step S1, the mass ratio of PLA and PCL is (9-1):1; the mass ratio of the total mass of PLA and PCL to the organic solvent is 1:(4-8); the organic solvent includes chloroform and dichloromethane; and the ultrasonic time is 3-8h.
7. The method for preparing a perovskite fluorescent composite material with shape memory properties according to claim 5, characterized in that: In step S2, the concentration of the PQD solution is 0.002-0.188 mol / ml; the volume ratio of the PQD solution to the gel solution is (0.05-1):1; the magnetic stirring time is 1-3 h, and the rotation speed is 300-1000 r / min; the ultrasonic time is 0.5-3 h, and the ultrasonic power is 35 kHz-50 kHz.
8. The method for preparing a perovskite fluorescent composite material with shape memory properties according to claim 5, characterized in that: In step S2, the preparation method of the PQD includes a hot injection method and a room temperature method; the PQD is dripped into the gel solution obtained in step S1 at a speed of 1 to 2 drops per second.
9. The method for preparing a perovskite fluorescent composite material with shape memory properties according to claim 5, characterized in that: In step S3, the volatilization molding method includes scraping, dripping or spin coating.
10. An application of the perovskite fluorescent composite material with shape memory properties as claimed in any one of claims 1 to 4, characterized in that: Including applications in 3D printing materials, anti-counterfeiting technology materials, and flexible materials.